Al-Rajhi: The Saudi Arabia Kingdom’s Glocal Bank - Rawashdeh, Osamah (IIUM Journal of Case Studies in Management, 2021)
Al-Rajhi as the name denotes belongs to the Al-Rajhi family, a Saudi Arabiaâ€™s wealthiest non-royals and is considered as among the world’s leading philanthropists. Think globally Act locally or â€œGlocalâ€ is the idea behind creating a platform for local and Saudi Islamic banking and finance entities to compete in the global atmosphere. In fact local Islamic banking and finance industry in Saudi Arabia gave this inspiration to go â€œGlocalâ€ and the AlRajhi got this inspiration to become both â€œGlocalâ€ as well as the global Islamic bank. In the event of achieving this goal, AlRajhi through its foreign branches came across many challenges to buck up especially in serving the international Muslim market segments. Nevertheless, incrementally, the bank has kept adding feather to its cap. Al-Rajhiâ€™s successful story started way back in 1978 as a banking and trading establishment which merged into "Al-Rajhi Trading and Exchange Corporation". In 1987, it converted into a joint stock company under the royal decree No. 59. Later, the company renamed itself to Al-Rajhi Banking and Investment Corp under the ministerial decision No. 1398, and finally in 2006, it changed its name to Al-Rajhi Bank. Currently, globally Al-Rajhi bank can also be found in Kuwait, Jordan and Malaysia.